THE FORMATION PROCESS AND SOCIAL STRUCTURE OF THE SOMANI STATE (Neo Science Peer Reviewed Journal, 2023)
This article describes the Samaritans, one of the most powerful countries in the history of the early Middle Ages. Information will also be provided about the state administration apparatus and governmental systems of this state, from government positions in the palace, considered the highest public position, to small government positions and their main functions. It discusses land ownership in the Samaritans, the types and functions of land owned for public services.